2011
DOI: 10.3109/00016357.2011.572290
|View full text |Cite
|
Sign up to set email alerts
|

Tubular occlusion of simulated hypersensitive dentin by the combined use of ozone and desensitizing agents

Abstract: The use of ozone gas is a viable adjunct to fluoride-containing desensitizers in enhancing tubular occlusion, but is not effective with oxalate desensitizers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…Despite the somewhat negative findings in our and previous studies regarding ozone treatment on DH, the powerful oxidising property of ozone might contribute to the treatment of DH, but with a different mode of action. Abdelaziz et al [9], suggested that ozone treatment of exposed dentin removes smear layers, opens up the dentinal tubules, broadens their diameter and facilitates the entrance of minerals. Mineral and substance both from saliva or from other desensitising agents, for example calcium and fluoride ions, enter the tubules easily and deeply effectively plugging the dentinal tubules and preventing the fluid exchange through these tubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the somewhat negative findings in our and previous studies regarding ozone treatment on DH, the powerful oxidising property of ozone might contribute to the treatment of DH, but with a different mode of action. Abdelaziz et al [9], suggested that ozone treatment of exposed dentin removes smear layers, opens up the dentinal tubules, broadens their diameter and facilitates the entrance of minerals. Mineral and substance both from saliva or from other desensitising agents, for example calcium and fluoride ions, enter the tubules easily and deeply effectively plugging the dentinal tubules and preventing the fluid exchange through these tubules.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting, novel approach may therefore be the use of ozone treatment in DH. In spite of promising results in the laboratory, where ozone has been suggested to enhance tubular occlusion and act as desensitizing agent [9], few clinical studies have been conducted to test the efficacy of this technology [10-12] . The aim of this single blind, randomised controlled clinical trial was therefore to investigate the effect of ozone treatment on DH.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone is used in many dental therapies including tissue regeneration and postsurgery healing,[ 3 ] tooth surface remineralization and treatment of early dental caries,[ 4 5 ] root canal disinfection,[ 6 ] periodontal pocket therapy,[ 7 ] teeth whitening and management of tooth sensitivity,[ 8 9 ] and pain control and temporomandibular joint treatment. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] However, these crystals are small in size and hence not effective in occluding the tubules. [ 2 ] This may be the reason for the significantly lesser depth of penetration of NaF (154.09 ± 25.16 μm) when compared to Groups 3 and 4. Similar results were obtained by Raafat Abdelaziz et al .,[ 2 ] who showed that fluoride treated specimens displayed significantly lower percentage of tubule occlusion compared to other experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…Dentin hypersensitivity is a commonly encountered, painful clinical condition for which no consistent remedy has been established. [ 1 2 ] Although various theories have been put forward over the years to explain the physiological mechanism behind this problem, hydrodynamic theory of dentinal sensitivity remains the most accepted theory till date. [ 3 ] Stimuli such as heat, cold, evaporation, osmotic, and pressure changes cause fluid movement within the dentinal tubules, thereby inducing sharp pain responses in the nerve fibers.…”
Section: Introductionmentioning
confidence: 99%